FINANCIAL SOUNDNESS EVALUATION OF SELECTED COMMERCIAL BANKS IN INDONESIA: AN APPLICATION OF BANKOMETER MODEL - Landjang, Xenia I. S.; Tumiwa, Johan (Journal of Asean Studies on Maritime Issues, 2017)
Derived from the public concern about which bank to choose to be work with because of many kinds of banks are available right now in the banking industry in Indonesia also because of the Asean Economic Community (AEC) era nowadays which is establishing a system of free-trading among ASEAN country, author wants to give a recommendation which banks are good to be work with also as a reference for the investors who are looking to invest especially in banking industry in Indonesia, using the new model developed by IMF in 2000 called Bankometer. It is using the 6 parameters of financial ratios which are; capital to asset; equity to asset; CAR; NPL; cost to income and loans to assets. This study examined 19 private owned banks with the criteria private owned bank with total assets Rp 50 trillion because of the availability of the bank and the published financial statements. The result shows all the 19 banks are termed into super sound bank for the last three years. The top three banks are: Bank of Tokyo Mitsubishi stood at the peak, followed by Citibank and BTPN.Keywords: Bankometer, Financial Soundness, Private-owned banks